2004
DOI: 10.1016/j.stam.2004.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular orbital calculations of hydrogen storage in carbon and boron nitride clusters

Abstract: Hydrogen gas storage ability in carbon and boron nitride (BN) clusters was investigated by molecular orbital calculations. From single point energy calculations, H 2 molecules would enter from hexagonal rings of C 60 and B 36 N 36 clusters and octagonal rings of B 24 N 24 cluster because of lower energy barrier. Chemisorption calculation of hydrogen for BN clusters showed that hydrogen bonding with nitrogen atoms was more stable than that with boron atoms. Stability of H 2 molecules in BN clusters seems to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22] One of the most basic arguments in these theoretical works is whether BN nanomaterials have site selectivity on adsorption of atomic hydrogen. Some reports mentioned that atomic hydrogen is adsorbed on B or N sites selectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19][20][21][22] One of the most basic arguments in these theoretical works is whether BN nanomaterials have site selectivity on adsorption of atomic hydrogen. Some reports mentioned that atomic hydrogen is adsorbed on B or N sites selectively.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports mentioned that atomic hydrogen is adsorbed on B or N sites selectively. [15][16][17][18][19] Mårlid et al 15 reported an adsorption energy difference of atomic hydrogen between B and N sites of hexagonal BN (h-BN). They applied DFT calculations to model structures of h-BN and found that adsorption at N sites is even more unstable than adsorption at B sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinpolarized NBO analysis of alkali encapsulated B 24 N 24 through DFT method also reported [21]. Many other investigations have been performed on B 24 N 24 nanocage to probe its chemical and physical properties [22][23][24][25]. Chemical concepts, reactivity indices and rules [26,27], stemming from density functional theory (DFT), such as frontier orbitals (HOMO/LUMO), electronegativity (chemical potential), global and local hardness and softness, Fukui function, electrophilicity index, hard and soft acid and base (HSAB), maximum hardness principle (MHP), etc., have attracted considerable interests in the literature in the last few decades.…”
Section: Introductionmentioning
confidence: 87%
“…For the chemisorption site of atomic hydrogen on h-BN, however, a couple of theoretical results are presented, which are apparently contradictory to each other. While some researchers claim that hydrogen atoms are site-selectively chemisorbed on electron-deficient boron atoms, [17][18][19] others claim N site-selectivity, 20 no site-selectivity, 21,22 or H cluster formation after B-H bond formation. 23 For experimental results, it is claimed that high energy plasma treatment or accelerated ion irradiation results in both B-H and N-H formation, 24,25 while the selective formation of the B-H bond was claimed by Koswattage et al upon atomic hydrogen exposure.…”
Section: Introductionmentioning
confidence: 99%